Front Matter Jurnal Litbang Industri Vol. 8 No. 1 Juni Tahun 2018 - Sofyan, Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2018)
Front Matter Jurnal Litbang Industri Vol. 8 No. 1 Juni Tahun 2018